Computer science for top level team sports - Lames, M. (International Journal of Computer Science in Sport, 2003)
The historical process of computer science in sports has arrived at a state where technical limitations are increasingly overcome by the general technological development. This allows to devote more time and effort to theoretical problems concerned for example with model building in sports. In order to find an appropriate description for training as well as for competition in game sports, there are many reasons to adopt a system view. While this idea is rather new for training, several approaches have been developed to model competition as a complex system. The actual agenda for computer science in team sports may be characterized by three projects: Real time position analysis is about to be ready for practical purposes, information technology will be further exploited in order to improve support for practice, and the search for a comprehensive model for training, skill level, and competition in team sports will be an important step to improve the practical impact of scientific service.